Student community engagement : insight from Australia / Ellen Chung and Hamish Coates - Chung, Ellen; Coates, Hamish (Universiti Teknologi MARA Cawangan Sarawak, 2018)
Student community engagement is a form of experiential education where students engage in activities that address community needs. This form of learning emphasizes collaboration between students, faculty, and the community partner. By using Student Community Engagement Benefits Questionnaire, data was collected from 151 students in four Australian universities. This study has identified the various community engagement activities they participated either in Australia or overseas; whether voluntary or compulsory. Analysis of variance and paired sample t-test showed that there was a statistically significant gain in Career, Diversity, Interpersonal and Civic skills among the respondents after the community engagement activities. By incorporating three demographic and contextual characteristics, analysis of covariance showed that the changes after community engagement in these four skills were not significant between the two types of projects (compulsory and voluntary projects). When data was analysed by age group of respondents, there was a significant difference after community engagement only in Civic skills. Analysis by community engagement durations also showed that there was a significant difference in Career skills, Interpersonal Skills and Civic skills. This paper sheds light on what students learn from community engagement in the context of Australian higher education